2007
DOI: 10.1016/j.neulet.2007.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Changes in vasoactive intestinal peptide and arginine vasopressin expression in the suprachiasmatic nucleus of the rat brain following footshock stress

Abstract: The neuropeptides, arginine vasopressin (AVP) and vasoactive intestinal polypeptide (VIP) are synthesized by neurons of the suprachiasmatic nucleus (SCN) of the hypothalamus and are important regulators of SCN function. Previous studies have demonstrated that acute exposure to stressors can disrupt circadian activity rhythms, suggesting the possibility of stress-related alterations in the expression of these neuropeptides within SCN neurons. In this study, we examined the effect of intermittent footshock stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Because all mice were entrained to 24‐h LD cycles before sacrifice, we consider that the differences observed between the groups reflect a long‐lasting effect of early light experience. Changes in AVP and VIP expression in the hypothalamus are associated with various physiological states and disorders, such as stress (47), depression (48) and hypertension (49) and, in some cases, alterations in the SCN are considered to precede the development of the disease. The results obtained in the present study are thus beginning to uncover the possibility that early light experience may not only have effects at the level of locomotor activity rhythm, but may also have effects on neuroendocrine systems.…”
Section: Discussionmentioning
confidence: 99%
“…Because all mice were entrained to 24‐h LD cycles before sacrifice, we consider that the differences observed between the groups reflect a long‐lasting effect of early light experience. Changes in AVP and VIP expression in the hypothalamus are associated with various physiological states and disorders, such as stress (47), depression (48) and hypertension (49) and, in some cases, alterations in the SCN are considered to precede the development of the disease. The results obtained in the present study are thus beginning to uncover the possibility that early light experience may not only have effects at the level of locomotor activity rhythm, but may also have effects on neuroendocrine systems.…”
Section: Discussionmentioning
confidence: 99%
“…Correlative studies have demonstrated that over 50% of patients with alcohol dependency also have anxiety-related or depression-related psychiatric disorders (13), and these types of disorders are often associated with an abnormal stress response. Interestingly, women alcoholics have a higher incidence of clinically diagnosed anxiety disorders compared with men alcoholics (19,59), possibly because of the inherent sex differences in the stress responses of the HPA axis (3,25). Furthermore, repeated episodes of acute EtOH exposure increased anxiety behaviors in peripubertal animals, as measured by increased latency to explore a novel object in the retention-based passive avoidance task (38).…”
mentioning
confidence: 99%
“…might be better inquired by the inclusion of 'bio-communicators', as termed by Tozuka et al, in the study design (37). Nuclear factor kappa B, which is suggested to play a regulatory role in prenatal stress-induced cognitive impairment, maternal vasoactive intestinal peptide, ghrelin, and oxytocin, known to be related to emotional stress in the mother rat and affecting the neural development of offspring as well as Protein Kinase C beta1 in the hippocampus resulting from prenatal restraint stress suggested to play an important role in the impairment of learning and memory abilities of offspring could be examples for further research (34,38,39). Additionally, measurement of hippocampal long-term potentiation is considered to be a reliable indicator of the direction of neurophysiologic changes underlying learning and memory induced by maternal stress of different intensities (35).…”
Section: Discussionmentioning
confidence: 99%